2006
DOI: 10.1182/blood-2006-08-013995
|View full text |Cite
|
Sign up to set email alerts
|

A phase 2/3 multicenter randomized clinical trial of ABX-CBL versus ATG as secondary therapy for steroid-resistant acute graft-versus-host disease

Abstract: Treatment for steroid-resistant acute graftversus-host disease (GVHD) has had limited success. ABX-CBL is a hybridomagenerated murine IgM monoclonal antibody against the CD147 antigen, weakly expressed on human leukocytes and up-regulated on activated lymphocytes. A prospective, multicenter, openlabel, randomized clinical trial comparing ABX-CBL to antithymocyte globulin (ATG) for treatment of steroid-resistant acute GVHD was conducted in 95 patients at 21 centers. Forty-eight patients received ABX-CBL daily f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
62
0

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(64 citation statements)
references
References 22 publications
0
62
0
Order By: Relevance
“…17 The results of the only other randomized multicenter trial comparison (ABX-CBL vs ATG) also provided similar rates nearly 10 years ago. 7 The current randomized trial provides evidence that, using current supportive treatment, the 1-year expected survival rate is within the 45%, which seems to be higher than the expected 30% rate usually reported. Other IL-2 and IL2-R targeted therapies have been used in the setting of SR aGVHD including denileukin diftitox or dacluzimab (alone or in combination with anti-tumor necrosis factor-a monoclonal antibodies).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…17 The results of the only other randomized multicenter trial comparison (ABX-CBL vs ATG) also provided similar rates nearly 10 years ago. 7 The current randomized trial provides evidence that, using current supportive treatment, the 1-year expected survival rate is within the 45%, which seems to be higher than the expected 30% rate usually reported. Other IL-2 and IL2-R targeted therapies have been used in the setting of SR aGVHD including denileukin diftitox or dacluzimab (alone or in combination with anti-tumor necrosis factor-a monoclonal antibodies).…”
Section: Discussionmentioning
confidence: 68%
“…1,5,6 Despite this unmet clinical need, it may be surprising that, to the best of our knowledge, only 2 randomized phase 2/3 studies have ever been performed in the setting of SR aGVHD. 7,8 Both studies showed that neither early introduction of antithymocyte globulins (ATG) nor the substitution of ATG by an investigational drug improved the dismal outcome for these patients.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, OS reported here is within the range of reported survival among alternative agents used for steroidrefractory aGVHD. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] MMF was overall well tolerated, with the majority of those treated here remaining on therapy without dose reduction or significant adverse events directly referable to this agent; only two patients required discontinuation of MMF on account of myelosuppression. However, though a direct causal role cannot be assigned to MMF, the overall burden of immunosuppression and related infectious complications certainly contributed to the morbidity and mortality seen in this series.…”
Section: Discussionmentioning
confidence: 99%
“…5,[8][9][10][11] A number of therapeutic agents directed at the immune cascade underlying aGVHD have shown modest activity in steroid-refractory aGVHD. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] Mycophenolate mofetil (MMF), whose metabolite mycophenolic acid inhibits the de novo synthesis of purines in lymphocytes, has probable efficacy in the treatment of aGVHD, based on three small case series that cumulatively reported 17 cases in which MMF was used for initial therapy for aGVHD, and 16 cases with glucocorticoidrefractory aGVHD. [31][32][33] Here, we report outcomes in a series of 27 recipients of allogeneic hematopoietic cell transplantation treated with MMF as salvage therapy for steroid-refractory aGVHD.…”
Section: Introductionmentioning
confidence: 99%
“…ABX-CBL was given intravenously at 0.1 mg/kg per day for 14 consecutive days; dependent upon treatment responses, "maintenance" for up to 3 cycles (2 infusions per week for 2 weeks) was allowed. 45 Disappointingly, the response rates did not differ between the 2 arms, and day-180 survival was nonsignificantly better in the ATG arm.Good responses were also obtained with the humanized antibody, HuM291 (visilizumab), directed at the invariant CD3 epsilon chain of the T-cell receptor. 34 Among 15 patients with steroidrefractory GVHD, 7 achieved complete and 8 partial responses.…”
mentioning
confidence: 91%